Experimental and numerical studies of laminated butt joint specimens with Aluminum butt straps under preload - Subramanya Sastry, Sringeri Srikanta; Nagaraju Reddy, Venkata Siva; Ramjeyathilagam, Kasi (Pure and Applied Science Advances, 2017)
Experimental and numerical investigations on laminated butt joint specimens (size 72 mm x 135 mm x 3.328 / 4.502 / 5.672 mm thickness) with Aluminium butt straps under preload are presented. Five specimens each of three different thickness using 6781 8HS S2 glass fabric with quasi-isotropic layup were fabricated, assembled and tested to study their failure behavior. The specimens with two bolts in parallel and series were designed to twice the width mentioned in ASTM D 5961/D 5961M – 08, fabricated by matched die moulding process for the study of bearing strength and ultimate load carrying capacity of a eight bolted butt joint. The width of the specimens, edge distance and pitch of the M6 fasteners were adjusted so as to be within the limits of the Instron testing machine with Zwick-Roell grips. The experimental results were compared with the numerical results of a 3D finite element model developed from a Catia model that incorporates a characteristic curve around the bolt holes of the butt joint. The points on the bearing failure boundary around each fastener hole was compared with the curve approximated using the least square method. It was observed that the theoretical characteristic curve has shown deviation to the curve fitted using least square method on the experimental data.